PENGARUH STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PRODUK UMKM STUDI TERHADAP TOKO IMAMGIFT.ART - Febriani Wahyusari Nurcahyanti; Siti Mudrikatul Faizah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Marketing strategy is a way to face business competition and an effort to increase product sales to UMKM. This research was conducted to find out how the marketing strategy using segmentation, targeting and positioning (STP) strategy analysis and SWOT analysis in the Imamgift.art Store business. The type of research used is qualitative with a descriptive approach. Data collection techniques using the method of observation, interviews and documentation. Interviews were conducted to informants who have been selected from purposive sampling technique, namely to an owner and several consumers who have purchased products at the Imamgift.art Store. The results of this study are the segmentation, targeting and positioning strategies that are carried out to make the marketing strategy more focused in delivering products to consumers so that it has an impact on increasing sales at the Imamgift.art Store. From the SWOT analysis, the suggested strategy to use is the SO (Strength Opportunity) strategy.